Managerial Competence of the Principal in Implementing Strategic Management in SMKN 1 Jantho and Al-Mubarkeya, Aceh Besar Regency - Ichsan, Ichsan; Yusrizal, Yusrizal; Bahrun, Bahrun (FKIP Universitas Lampung, 2021)
The purpose of this study was to determine the formulation of vision and mission and the implementation of strategic management. Data collection techniques are interviews, observation, and documentation. Research subjects are Principal, Teacher, School Committee, and the Industrial World. The results showed that: (1) Strategic management planning begins with deliberation of all school personnel by considering the state of the internal environment and the environment; (2)Implementation of strategic management is carried out by observing the environment by considering the internal environment and external environment, pouring strategies into learning and training programs and implementing the strategies carried out by arranging the organizational structure, implementing industrial work practices, and carry out human resource development; (3) Evaluation or control was carried out by involving all of the school personnel in the short, medium and long terms by using evaluation instruments compiled on the basis of eight national education standards.Keywords: managerial competence, school principal, teacher performance.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202113